Evaluation of hsp65 Nested PCR-Restriction Analysis (PRA) for Diagnosing Tuberculosis in a High Burden Country - Macente, Sara; Leite, Clarice Queico Fujimura [UNESP]; Barreto Santos, Adolfo Carlos [UNESP]; Dias Siqueira, Vera Lucia; Cosmo Machado, Luzia Neri; Marcondes, Nadir Rodrigues; Hirata, Mario Hiroyuki; Crespo Hirata, Rosario Dominguez; Cardoso, Rosilene Fressatti (Hindawi Publishing Corporation, 2013)
Current study evaluated the hsp65 Nested PCR Restriction Fragment Length Polymorphism Analysis (hsp65 Nested PCR-PRA) to detect and identify Mycobacterium tuberculosis complex directly in clinical samples for a rapid and specific diagnosis of tuberculosis (TB). hsp65 Nested PCR-PRA was applied directly to 218 clinical samples obtained from 127 patients suspected of TB or another mycobacterial infection from July 2009 to July 2010. The hsp65 Nested PCR-PRA showed 100% sensitivity and 95.0 and 93.1% specificity in comparison with culture and microscopy (acid fast bacillus smear), respectively. hsp65 Nested PCR-PRA was shown to be a fast and reliable assay for diagnosing TB, which may contribute towards a fast diagnosis that could help the selection of appropriate chemotherapeutic and early epidemiological management of the cases which are of paramount importance in a high TB burden country.